William Bell Clark collection - Clark, William Bell, 1889-1968.
Papers and records relating to British and American naval operations during the American Revolution. Includes logs from HMS Fowey (Sloop of war), HMS Kingfisher (Sloop of war), HMS Liverpool (Warship), HMS Roebuck (Warship), and the USS Wasp (Schooner); records of the USS Lexington (Brig); correspondence of Benjamin Franklin; papers of or relating to Capt. John Young; copies of other letters, newspaper clippings, and orders; and speech and article written by Clark.
Chiefly photocopies of typewritten transcripts made from originals in various repositories.
Naval historian.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: Franklin, Benjamin, -- 1706-1790 -- Correspondence; Young, John, -- -1781.; Great Britain. -- Royal Navy -- History -- 18th century; United States. -- Continental Navy; Fowey (Sloop of war); Kingfisher (Sloop of war); Lexington (Brig : 1777); Liverpool (Warship); Roebuck (Warship); Wasp (Schooner); Ship's papers -- 18th century; United States -- History -- Revolution, 1775-1783 -- British forces; United States -- History -- Revolution, 1775-1783 -- Naval operations; Naval historians